Pricing in response to new information: The case of betting markets - Kai Fischer; W. Benedikt Schmal (Economic Inquiry, 2024)
Abstract Markets are information aggregators. But how do they incorporate new data into their pricing? We examine the response of prediction markets to a novel information shock in a quasi-natural experiment: How did the absence announcements of elite soccer players influence the betting odds of affected matches? Analyzing the first four statistical moments of 117,174 odds from 32 bookmakers, we identify initial inertia followed by a lagged reaction that we cannot reason with learning. Our findings raise questions about how bettors and bookmakers incorporate new information into their beliefs. It has broader implications regarding information processing in markets.
Keywords: 330; belief updating; betting markets; betting odds; forecasting errors; information shocks; prediction markets; pricing